ASEAN Economic Community : a model for Asia-wide regional integration? - Aflouk, Nabil 1979- (Palgrave Macmillan, 2016)
The launch of the ASEAN Economic Community raises key issues: the deepening of regional trade and the associated problem of exchange rate management. This volume questions the capacity of a shallow institution to deal with complex impacts on employment and inequality. Contributors analyze ASEAN's potential and weakness in readable terms.